Coordinating the Reverse Factoring System: Buying Back and Bargaining - Shengying Zhao; Huan Zhou (Mathematics)
Reverse factoring is a retailer-led supply chain financing system that can enhance liquidity of suppliers and reduce factoring fraud. This paper proposes a bargaining game theory model to analyze the profit distribution in reverse factoring for a two-echelon supply chain system that comprises a core retailer and a capital-constrained supplier. By taking into account the retailer’s credit loss risk, the impact of buying back and bargaining is investigated. Our study shows that in reverse factoring without buying back, the supplier would rather not bargain but the retailer would like to negotiate the wholesale price if the supplier’s bargaining power is low. If buying back exists and the supplier’s bargaining power is low, the retailer is also willing to negotiate the wholesale price. If there is no bargaining but the supplier takes a large portion of the supply chain’s profit, buying back is preferred. Furthermore, when there is bargaining on the wholesale price, both supplier and retailer can benefit from buying back. In addition, bargaining on the buy-back price in reverse factoring is bargaining-proof. Our study first contributes to the growing body of literature on reverse factoring and bargaining game theory. Two managerial implications for reverse factoring also emerge from the study. We find that bargaining should be considered if the supplier tends to coordinate the supply chain financing system by buying back the retailer’s unsold products. In addition, both supplier and retailer should negotiate the wholesale price as they cannot benefit from bargaining on the buy-back price.